Trematocine-derived antimicrobial peptides from the Antarctic fish Trematomus bernacchaii: potent antibacterial agents against ESKAPE pathogens - Squitieri, Damiano; Massaro, Federica; Graziano, Monica Mollica; Borocci, Stefano; Cacaci, Margherita; Di Vito, Maura; Porcelli, Fernando; Rosato, Roberto; Ceccacci, Francesca; Sanguinetti, Maurizio; Buonocore, Francesco; Bugli, Francesca (Frontiers in Microbiology, 2024)
Introduction This study investigated the interaction with membrane mimetic systems (LUVs), bacterial membranes, the CD spectra, and the bactericidal activity of two designed trematocine mutants, named Trem-HK and Trem-HSK. Mutants were constructed from the scaffold of Trematocine (Trem), a natural 22-amino acid AMP from the Antarctic fish Trematomus bernacchii, aiming to increase their positive charge.The selectivity of the designed AMPs towards bacterial membranes was improved compared to Trematocine, verified by their interaction with different LUVs and their membranolytic activity. Additionally, their α-helical conformation was not influenced by the amino acid substitutions. Our findings revealed a significant enhancement in antibacterial efficacy against ESKAPE (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacteriaceae family) pathogens for both Trem-HK and Trem-HSK.Results Firstly, we showed that the selectivity of the two new designed AMPs towards bacterial membranes was greatly improved compared to Trematocine, verifying their interaction with different LUVs and their membranolytic activity. We determined that their -helical conformation was not influenced by the amino acid substitutions. We characterized the tested bacterial collection for resistance traits to different classes of antibiotics. The minimum inhibitory and bactericidal concentration (MIC and MBC) values of the ESKAPE collection were reduced by up to 80% compared to Trematocine. The bactericidal concentrations of Trematocine mutants showed important membranolytic action, evident by scanning electron microscopy, on all tested species. We further evaluated the cytotoxicity and hemolytic activity of the mutants. At 2.5 μM concentration, both mutants demonstrated low cytotoxicity and hemolysis, indicating selectivity towards bacterial cells. However, these effects increased at higher concentrations. Discussion Assessment of in vivo toxicity using the Galleria mellonella model revealed no adverse effects in larvae treated with both mutants, even at concentrations up to 20 times higher than the lowest MIC observed for Acinetobacter baumannii, suggesting a high potential safety profile for the mutants.This study highlights the significant improvement in antibacterial efficacy achieved by increasing the positive charge of Trem-HK and Trem-HSK. This improvement was reached at the cost of reduced biocompatibility. Further research is necessary to optimize the balance between efficacy and safety for these promising AMPs.